β-blockers and metabolic modulation: unraveling the complex interplay with glucose metabolism, inflammation and oxidative stress - Drygała, Szymon; Radzikowski, Michał; Maciejczyk, Mateusz (Frontiers in Pharmacology, 2024)
The growing burden of metabolic disorders manifested by hypertension, type 2 diabetes mellitus, hyperlipidemia, obesity and non-alcoholic fatty liver disease presents a significant global health challenge by contributing to cardiovascular diseases and high mortality rates. Β-blockers are among the most widely used drugs in the treatment of hypertension and acute cardiovascular events. In addition to blocking the receptor sites for catecholamines, third-generation β-blockers with associated vasodilating properties, such as carvedilol and nebivolol, provide a broad spectrum of metabolic effects, including anti-inflammatory and antioxidant properties and a favorable impact on glucose and lipid metabolism. This review aims to report the impact of β-blockers on metabolic modulation based on available literature data. We present an overview of β-blockers and their pleiotropic properties, discuss mechanisms by which these drugs affect cellular metabolism and outline the future perspectives. The influence of β-blockers on glucose metabolism, insulin sensitivity, inflammation and oxidative stress is complex and varies depending on the specific β-blocker used, patient population and underlying health conditions. Recent evidence particularly highlights the potential role of vasodilatory and nitric oxide-mediated properties of nebivolol and carvedilol in improving glycemic control, insulin sensitivity, and lipid metabolism and mitigating oxidative stress and inflammation. It suggests that these drugs may be potential therapeutic options for patients with metabolic disorders, extending beyond their primary role in cardiovascular management.